2018
DOI: 10.1016/j.neuroscience.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Projections to the Cochlear Nucleus are Redistributed in Tinnitus

Abstract: Tinnitus alters auditory-somatosensory plasticity in the cochlear nucleus (CN). Correspondingly, bimodal auditory-somatosensory stimulation treatment attenuates tinnitus, both in animals and humans (Marks et al., 2018). Therefore, we hypothesized that tinnitus is associated with altered somatosensory innervation of the CN. Here, we studied the expression of vesicular glutamate transporters 1 and 2 (VGLUT1 and VGLUT2) in the CN, which reveals glutamatergic projections from the cochlea as well as somatosensory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 62 publications
(127 reference statements)
4
40
1
2
Order By: Relevance
“…In the present study, the right ear of each rat was protected, and the ABR recording confirmed that hearing loss was not apparent on the right side. The present study employed TTS to induce cochlear insults and found reductions in VGLUT1 levels after noise exposure, which is consistent with previous findings (15,21,32,33). In addition, comparisons of the tinnitus and non-tinnitus groups revealed that the tinnitus group exhibited a greater decrease in VGLUT1 expression levels; this occurred earlier (i.e., in the first week after noise exposure) compared with the non-tinnitus group, which showed a decrease in VGLUT1 level at 2 weeks.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, the right ear of each rat was protected, and the ABR recording confirmed that hearing loss was not apparent on the right side. The present study employed TTS to induce cochlear insults and found reductions in VGLUT1 levels after noise exposure, which is consistent with previous findings (15,21,32,33). In addition, comparisons of the tinnitus and non-tinnitus groups revealed that the tinnitus group exhibited a greater decrease in VGLUT1 expression levels; this occurred earlier (i.e., in the first week after noise exposure) compared with the non-tinnitus group, which showed a decrease in VGLUT1 level at 2 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, changes in neural input can be observed by assessing changes in VGLUT expression. A number of studies have demonstrated that cross-modal compensation occurs in the ipsilateral DCN after cochlear insults, as evidenced by decreases in VGLUT1, which reflects auditory inputs, and increases in VGUT2, which reflects non-auditory inputs (15,16,21,34).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations